A study of mt-dna hypervariable region 1 (HVI) sequence polymorphism on residents of Johor in Malaysia - Lari, Alireza (2013)
In the past few decades, lots of studies were carried out to find a way for searching relationships among various races of human beings in understanding their relatedness within a population. This study has been performed to generate DNA sequence data with a view to identifying genetic marker and using them in detecting a population in a particular area, such as, in our case, Johor, Malaysia. Mitochondrial DNA (MtDNA) sequence is usually used to detect relatedness between the races within a human population of particular region. The sequence of the region including hypervariable region 1 (HV1, nt16024-16365) and hypervariable region 2 (HV2, nt73-340) are typically used in forensic study. In this study, polymorphisms of (HV1) were investigated to discover a potential forensic marker for detecting different races. In this research PCR amplification after DNA extraction was done to detect the sequence of (HV1). Then, comparisons between Anderson reference - The Cambridge Reference Sequence (rCRS) for human mitochondrial DNA - and the sequences obtained in the current study was done. The results showed the 48 nucleotide variations within the sequence of around 340 bp nucleotides can be used as a genetic marker in forensic study among Malay population of Johor.